DIGITAL TOOLS FOR ENGLISH LANGUAGE LEARNING IN PHARMACY EDUCATION PROGRAMS - Mariana, Mariana; Purwana, Rudi; Novianti, Winda; Chaniago, Ani Deswita (EXCELLENCE: Journal of English and English Education, 2023)
In response to the increasing demand for effective English language communication skills in the pharmaceutical domain, this study explores the integration of digital tools within pharmacy education programs. The globalized nature of the pharmaceutical industry necessitates a thorough examination of innovative strategies to enhance language proficiency among students. Utilizing a mixed-methods approach, the research combines quantitative assessments and qualitative analyses to investigate the impact of various digital tools on language learning outcomes, student engagement, and the practical application of acquired skills.The quantitative component involves evaluating language proficiency levels through surveys and assessments, providing a quantitative measure of the effectiveness of digital tools. Concurrently, qualitative analyses, including interviews and focus group discussions, aim to uncover insights into learner experiences, preferences, and the challenges associated with integrating digital tools into language learning curricula within pharmacy education programs. The study's significance lies in its potential to inform educators, curriculum developers, and policymakers about the benefits of leveraging digital tools for English language learning in pharmacy education. By tailoring strategies to enhance communication skills, the research seeks to prepare future pharmacy professionals to navigate the diverse linguistic landscape of the pharmaceutical industry. The findings contribute to the ongoing discourse on innovative teaching methodologies, providing actionable insights for stakeholders committed to fostering language proficiency and effective communication in pharmacy education programs.